HIGHER ORDER THINKING SKILLS IN CRITICAL READING CLASS: AN ANALYSIS ON STUDENTS’ PERCEPTION - Tahir, Annisa Mujahidah; Farahdiba, Syarifah; Sunra, La (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This study aims to explore students’ perception toward Higher Order Thinking Skills in Critical Reading class. To achieve the research objective, the researcher used a descriptive study in the form of a qualitative design. The data were collected through one-to-one, semi-structured interviews conducted through mobile phone calls. The study focused on five students from the English Education Study Program's Class A 2021 who were enrolled in a critical reading class during their second semester. Based on the result of the study, the researcher found that in the critical reading class, the three upper levels of cognitive skills proposed by Bloom, which are considered as part of higher order thinking skills (HOTS), were applied in the form of activities such as text analysis, statement and argument validation, and paraphrasing. Students’ perception indicated that the three activities improved their ability in critical reading. However, throughout the course, the students faced some difficulties since the course was conducted online. The lecturer used the same lecturing style, had never given them feedback, and there was no discussion session for the students to share their ideas about the text in the module given. The lack of vocabulary was also mentioned as one of the obstacles experienced by the students during the critical reading class.